Interface: the metaphor as metaphor (KULT_online, 2016)
The anthology Schnittstellen. Die Gegenwart des Abwesenden, edited by Katharina Hoins, Thomas Kühn, und Johannes Müske, deals with the concept of interface as a metaphor for overlapping contact surfaces or boundaries which determine the way we perceive reality and the world. Ten contributions from cultural anthropology, arts, cultural studies, history, Islam studies, computer science, geography, and folklore studies analyse different forms and functions of interface, while sharing the interest for the production of knowledge in everyday, technical, and academic practices. The project succeeds in applying interface from different perspectives as a generic term without making of it an inflationary metaphor.